Regular Khat (Catha edulis) chewing is associated with elevated diastolic blood pressure among adults in Butajira, Ethiopia: A comparative study - Gedif Teferi; Getahun Workineh; Tesfaye Fikru (BMC, 2010)
Abstract Background Fresh leaves and buds of the Khat plant (Catha edulis) contain Cathinone, an amphetamine like alkaloid responsible for its pharmacological action. Chewing of Khat has been associated with a transient rise in blood pressure and heart rate in experimental studies. Few studies examined the effect of regular or frequent Khat chewing on blood pressure at the population level. This study was conducted to examine the association of regular Khat chewing with blood pressure among adults. Methods We compared systolic and diastolic blood pressure of adults 35-65 years of age who reported regular chewing of Khat during the preceding five years to those who never chewed Khat during the same period. Study participants were recruited from purposively selected urban and rural villages of Butajira District in Ethiopia. The comparative groups, chewers (334) and non-chewers (330), were identified from among the general population through a house-to-house visit using a screening questionnaire. They were frequency-matched for sex and age within a five-year range. Data were collected through structured interviews and physical measurements including blood pressure, weight and height. Results The prevalence of hypertension was significantly higher among Khat chewers (13.4%) than non-chewers (10.7%), odds ratio (OR) = 1.66 (95% confidence interval (CI) 1.05, 3.13). A considerably high proportion of chewers (29.9%) than non-chewers (20.6%) had sub-optimal diastolic blood pressure (> 80 mmHg). The mean (sd) diastolic blood pressure was significantly higher among Khat chewers [75.0 (11.6)] than non-chewers [72.9 (11.7)], P < 0.05. Similarly, Khat chewers had significantly higher mean (sd) heart rate [76.3 (11.5)] than non-chewers [73.9 (12.6)], P < 0.05. There was no significant difference in mean systolic blood pressure between the two groups. Conclusion Regular chewing of Khat is associated with elevated mean diastolic blood pressure, which is consistent with the peripheral vasoconstrictor effect of Cathinone. Regular Khat chewing may have sustained effects on the cardiovascular system that can contribute to elevated blood pressure at the population level.